Thrombin Interaction with Platelet GPIB: Role of the Heparin Binding Domain - De Candia, Erica; De Cristofaro, Raimondo; De Marco, Lulgi; Mazzucato, Moreno; Picozzi, Matilde; Landolfi, Raffaele (Thrombosis and Haemostasis, 1997)
The platelet membrane glycoprotein lb (Gplb) has a high affinity binding site for α-thrombin whose occupancy is thought to positively modulate the thrombin-induced platelet activation. In this study, aimed at further characterizing the thrombin-GpIb interaction, two thrombin anion exosites referred to as “heparin binding site” (HBS) and “fibrino#gen recognition site” (FRS) were investigated as the possible domains involved in Gplb binding. The role of thrombin HBS was explored by performing binding measurements of 125I-α-thrombin to purified glycocalicin (GC), the extracytoplasmic portion of Gplb, in the presence of heparin as well as after chemical modifications of the thrombin heparin binding site (thrombin-HBS phosphopyridoxylation). These studies showed that a) thrombin binding to GC could be competitively inhibited by heparin and b) the equilibrium association constant for thrombin-GC interaction was reduced up to ten-fold by chemical modifications at the HBS. On the other hand, the role of FRS in the thrombin-GC interaction could be excluded by other experiments showing that GC in solution could not influence the interaction of α-thrombin with two substrates which bind to both the catalytic site and the fibrinogen recognition site: 1) the thrombin receptor peptide 38-60 (TR, L38-E60) and 2) the A α-chain of fibrinogen. Altogether these results demonstrated that GC interaction with thrombin involves the enzyme heparin binding site, whereas the fibrinogen recognition site does not play a significant role.